Assessment of English Foreign Language Learners: MOOC Material Resume and Review of Online Professional English Network (OPEN) - Misnawati, Misnawati (Elsya : Journal of English Language Studies, 2022)
As a personal research note, this paper presents the summary and review of the course material "Assessment of English Language Learners" from the author's participation in the Massive Open Online Course (MOOC) program offered by the U.S. Department of State as the Online Professional English Network (OPEN). This article is suitable for practical tests for ESL/EFL teachers in classes where students learn English as a second language. It aims to fill the lack of literature on assessing English Language Learners, especially regarding meaningful and purposeful assessment studies in L2 language classes. This paper serves the information as a contribution to 1) determine a meaningful assessment; 2) collect and use data to use the right assessment; 3) select the types of alternative assessment; 4) foster students' motivation and engagement through assessment; and 5) making assessment fun. This paper's contributions will supplement teachers in determining the most appropriate assessment in line with their students' needs. In addition, assessment should act as an evaluation tool and be turned into something fun in the classroom so that students can get many benefits at once, namely learning experiences and learning outcomes. This article is recommended for practical assessments for EFL teachers in English second language learning classes.